Liquid bio-fertilizer for fruit tree and preparation method thereof - LIU LUOXIAN (2017)
The invention discloses a special liquid bio-fertilizer for a fruit tree and a preparation method thereof. Compared with the prior art, the special liquid bio-fertilizer for the fruit tree is safe and nontoxic, has a wide variety of functions, can rapidly improve the status of nutrient supply to the fruit tree, promotes reproductive growth and nutritional growth of the fruit tree, enables the body of the fruit tree to be strong, reduces the usage amount of fertilizer, enhances the utilization rate of fertilizer, improves the fruit output and quality of the fruit tree, has high social benefits, economic benefits and ecological benefits and is worth promotion and application. 本发明公开了种果树专用液体生物肥及其制备方法。相对于现有技术，本发明所得的果树专用液体生物肥，安全无毒，功能广泛，能迅速改善果树养分供应状况，促进果树生殖生长和营养生长，促进果树树体健壮，减少肥料用量，提高肥料利用率，提高果树果品产量及品质，具有很高的社会效益、经济效益和生态效益，值得推广应用。